2017
DOI: 10.1016/j.brainres.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression in early postnatal monoamine oxidase A knockout mice

Abstract: We reported previously that monoamine oxidase (MAO) A knockout (KO) mice show increased serotonin (5-hydroxytryptamine, 5-HT) levels and autistic-like behaviors characterized by repetitive behaviors, and anti-social behaviors. We showed that administration of the serotonin synthesis inhibitor para-chlorophenylalanine (pCPA) from post-natal day 1 (P1) through 7 (P7) in MAO A KO mice reduced the serotonin level to normal and reverses the repetitive behavior. These results suggested that the altered gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Anatomically, MAO-A knockout mice have reduced levels of the serotonin transporter (SERT) in the dorsal raphe [ 17 ], as well as higher somatosensory and lower entorhinal cortical activation as compared to wildtype controls [ 21 ]. These anatomical alterations are accompanied with modified gene expression associated with neurodevelopment, apoptosis, and cognitive function which may be related to the behavioral and anatomical abnormalities reported with altered serotonin levels during development [ 22 ]. By contrast, MAO-B knockout mice display neither aberrant behavior nor detectable changes in monoamines, with the exception of increased levels of phenylethylamine [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomically, MAO-A knockout mice have reduced levels of the serotonin transporter (SERT) in the dorsal raphe [ 17 ], as well as higher somatosensory and lower entorhinal cortical activation as compared to wildtype controls [ 21 ]. These anatomical alterations are accompanied with modified gene expression associated with neurodevelopment, apoptosis, and cognitive function which may be related to the behavioral and anatomical abnormalities reported with altered serotonin levels during development [ 22 ]. By contrast, MAO-B knockout mice display neither aberrant behavior nor detectable changes in monoamines, with the exception of increased levels of phenylethylamine [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying the neurochemical changes, these mice exhibit abnormal fear conditioning and alterations in hippocampal long-term potentiation [ 18 ]. Similar to the MAO-A knockout mice, MAO-A/B knockout mice display increased aggression and anxiety-like behaviors and have been proposed as a model of autism spectrum disorder [ 15 , 16 , 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional in vitro and in vivo studies have also found evidence for the roles of neurexins in ASD. Monoamine oxidase A knockout (KO) mice, which are an animal model for autism, exhibited downregulated levels of both neurexin 1 and neurexin 2 [55]. Furthermore, mice colonized with the microbiota of ASD patients showed differential splicing of NRXN2 [59].…”
Section: In Vitro and In Vivo Models Of Diseasementioning
confidence: 99%